O ensino-aprendizagem de matemática financeira utilizando ferramentas computacionais: uma abordagem construcionista - Leme, Nelson Dias (2007)
This work aims to contribute to the investigation of the impact of a constructionist approach to the use of electronic spreadsheets on the teaching and learning of topics related to Financial Mathematics. To this end, a teaching experiment was designed which involved students in the construction of their own formulas, using spreadsheets, for calculating interests and future values of investments, under regimes of both simple and compound rates. The constructionist conceptions of Papert provided a theoretical base for the development of the activities. The methodology adopted for the study was modelled according to the design-based research methodologies. Two phases of experimentation were elaborated. The first phase involves students initiating their studies in Financial Mathematics in working on a set of activities with spreadsheets, and then completing a series of paper and pencil tasks. In the second phase, to provide a basis for comparing the approach adopted with the more usual practice of giving students previously defined formulae for calculating interest, the paper and pencil task were also administered to a group of students who has previously studied Financial Mathematics. The analysis of data followed the cycle of description-execution-reflectiondebugging- description described by Valente. According to these analyses, the formulae constructed by the students and implemented on the computer served as computational models providing feedback and enabling simulations of various possible situations. This in turn allowed students to engage in a cycle of expression, evaluation and reflection of the mathematical domain in question